Teaching Effectiveness of Adjunct Built-In Clinical Instructors in Clinical Settings: Impact on Nursing Students’ Satisfaction and Self-Confidence Learning - Espina, Shirley; Espina, Sedfrey Keith (International Journal of Sustainability and Advanced Integrated Research, 2026)
Clinical instruction is essential in nursing education as it bridges theoretical learning with patient care. In the Philippines, adjunct-built-in clinical instructors—hospital-based nurses who also teach—are increasingly relied upon to address faculty shortages and clinical placement demands. This study aimed to assess their teaching effectiveness and examine its relationship with nursing students’ satisfaction and confidence in clinical practice. A descriptive-correlational design was employed involving 364 nursing students from Levels 2 to 4 at a university in Quezon City, all with prior exposure under adjunct-built-in clinical instructors. Data was collected using the Nursing Clinical Teacher Effectiveness Inventory and the Student Satisfaction and Self-Confidence in Learning Scale, and analyzed through descriptive statistics, Pearson correlation, and multiple regression. Students rated instructors highly effective across supervision, organization, teaching skills, assessment, and professional behavior (means 4.50–4.74, “Always”). Learners reported strong satisfaction (M = 4.62, SD ≈ 0.52) and confidence (M = 4.54, SD ≈ 0.55). Significant positive correlations were found between teaching effectiveness and satisfaction (r = 0.682, p < .001), teaching efficacy and confidence (r = 0.645, p < .001), and satisfaction and confidence (r = 0.701, p < .001). Regression analysis confirmed teaching effectiveness and satisfaction as predictors of confidence, explaining 62.3% of the variance. Effective adjunct-built-in clinical instructors foster satisfaction, confidence, and readiness for practice, underscoring their critical role in nursing education. This study contributes to United Nations Sustainable Development Goal 3 (Good Health and Well-being) by enhancing the preparation of competent nurses who can deliver high-quality patient care, thereby supporting healthier communities.